(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The article considers the approaches to ensuring the strategic resilience and sustainability of the Russian economy undergoing now digital transformation, which is becoming one of the most important priorities for the country’s development. The aim of the research is to theoretically substantiate directions and mechanisms for ensuring sustainability of the national economy in the process of digital transformation and to identify necessary prerequisites for overcoming Russia’s technological inferiority compared with the most developed countries and for maintaining competitiveness in the face of global changes and challenges. The primary research method used to address the topic is the interdisciplinary approach to considering economic sustainability in the context of compatibility of the functional and development parameters of the national economy to the varying conditions of the global economic environment. In the research, the authors used methods of institutional analysis and a systemic approach to the economic theory, which allowed them to identify internal discrepancies between the elements of the current economic system of the Russian Federation and the global processes. The article contains statistical data on the dynamics of the main economic indicators of the Russian Federation, considers different points of view on the studied problem, and identifies necessary prerequisites for overcoming the technological inferiority of the Russian economy compared with the most developed economies. Materials of this article have a definite practical value for different levels of government agencies, as they describe a methodological approach to analyzing and monitoring the sustainability potential of economic systems under the conditions of global changes.